Efeito de casca de camarão, hidrolisado de peixe e quitosana no controle da murcha de Fusarium oxysporum f.sp. chrysanthemi em crisântemo - Pinto, Zayame Vegette [UNESP] (2010)
The incorporation of shrimp peelings and fish hydrolyzate into a pine-bark container medium and an aerial spray of chitosan were investigated for the control of Fusarium wilt of chrysanthemum. Disease severity was evaluated by means of a six-category scale (0 - healthy plant to 5 - dead plant) at 8, 12, 15 and 20 weeks after planting in experiments with shrimp peelings and fish hydrolyzate, and after 18 weeks in the chitosan experiment. The total microbial activity of the container media was evaluated (by fluorescein diacetate hydrolysis), physicochemical attributes of the media were assessed, and plant growth components were measured. Incorporation of shrimp peelings into the pine-bark medium at 4% (v/v) suppressed wilt, but at 5% the plants exhibited symptoms of phytotoxicity and died. The suppression of Fusarium wilt was possibly due to physicochemical and biological changes in container medium induced by the shrimp peel. Given that the concentration which was phytotoxic was only slightly higher than the concentration which suppressed wilt and promoted plant growth, caution is needed in any use of shrimp peelings for wilt control. The fish hydrolyzate increased wilt severity as the concentration was increased. No consistent effects were found of chitosan applied to the aerial parts of the plant.